Banking euro area stress test model - Katarzyna Budnik; Mirco Balatti Mozzanica; Ivan Dimitrov; Johannes Groß; Michael Kleemann; Tomas Reichenbachas; Francesco Sannà; Andrei Sarychev; Nadežda Siņenko; Matjaz Volk (European Central Bank (ECB), 2020)
The Banking Euro Area Stress Test (BEAST) is a large scale semi-structural model developed to assess the resilience of the euro area banking system from a macroprudential perspective. The model combines the dynamics of a high number of euro area banks with that of the euro area economies. It reflects banks' heterogeneity by replicating the structure of their balance sheets and profit and loss accounts. In the model, banks adjust their assets, interest rates, and profit distribution in line with the economic conditions they face. Bank responses feed back to the macroeconomic environment affecting credit supply conditions. When applied to a stress test of the euro area banking system, the model reveals higher system-wide capital depletion than the analogous constant balance sheet exercise.
Keywords: E37; E58; G21; G28; 330; macro stress test; macroprudential policy; banking sector deleveraging; real economy-financial sector feedback loop